2019
DOI: 10.1152/ajprenal.00260.2018
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-secreted TGF-β1 contributes to fibroblast activation and ureteral stricture after ablation injury

Abstract: Iatrogenic injury to the healthy ureter during ureteroscope-guided ablation of malignant or nonmalignant disease can result in ureteral stricture. Transforming growth factor (TGF)-β1-mediated scar formation is considered to underlie ureteral stricture, but the cellular sources of this cytokine and the sequelae preceding iatrogenic stricture formation are unknown. Using a swine model of ureteral injury with irreversible electroporation (IRE), we evaluated the cellular sources of TGF-β1 and scar formation at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…To prove this theory right, the immunohistochemical expression of TGF-β was assessed in histological sections of lungs with BLM-induced pulmonary fibrosis. As expected, untreated animals presented the greatest counts of TGF-β-expressing cells, which agrees with other studies previously reported [ 56 , 82 , 83 ]. The significant decrease in pulmonary cells expressing TGF-β in EOCW-treated groups at 100 and 200 mg/kg, as well as in the deflazacort-treated group, is fully supported by the analysis of α-SMA-positive cells, attesting to the close relation between this cytokine and myofibroblast differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To prove this theory right, the immunohistochemical expression of TGF-β was assessed in histological sections of lungs with BLM-induced pulmonary fibrosis. As expected, untreated animals presented the greatest counts of TGF-β-expressing cells, which agrees with other studies previously reported [ 56 , 82 , 83 ]. The significant decrease in pulmonary cells expressing TGF-β in EOCW-treated groups at 100 and 200 mg/kg, as well as in the deflazacort-treated group, is fully supported by the analysis of α-SMA-positive cells, attesting to the close relation between this cytokine and myofibroblast differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory cells and other epithelial and mesenchymal cells activated by inflammatory cytokines are the major sources of TGF-β. Therefore, drugs such as steroids and cyclooxygenase inhibitors have been considered effective in reducing inflammatory cytokines, such as TGF-β, and consequently attenuate collagen deposition [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…M2 type TAMs can activate CAFs and thus help tumor progression (247). In addition, M2 macrophages can influence the MMT of fibroblasts, resulting in enhanced reactivity (238).…”
Section: Reciprocal Interactionsmentioning
confidence: 99%
“…However, there are few reports that macrophages activate fibroblasts. Ueshima, et al [ 35 ] demonstrated that TGF-β1 secreted from macrophages promoted fibroblast differentiation and scar formation in the ureter. To the best of our knowledge, this study is the first to confirm the activation of CAFs by TAMs in the TME.…”
Section: Discussionmentioning
confidence: 99%